Analisis Yuridis Perlindungan Hukum Terhadap Notaris Sebagai Pejabat Umum dalam Sistem Peradilan Pidana Terkait Kewenangan Membuat Akta Otentik (Studi Penelitian Di Kota Batam) - Andri Gotama; Ramon Nofrial; Fadlan Fadlan; Soerya Respationo; Erniyanti Erniyanti (UNES Law Review, 2023)
Notaries are public officials who are appointed and dismissed by the state through the Minister of Law and Human Rights of the Republic of Indonesia. Apart from the duties and obligations, Notaries also have the authority regulated in the Notary Position Law and receive legal protection from the state. The problems of this research: What is the relationship between Notaries as Public Officials in the criminal justice system regarding the authority to make authentic deeds, What is the legal protection for Notaries as Public Officials in the criminal justice system related to the authority to make authentic deeds, and the role of the Notary Honorary Council in providing legal protection for Notaries as Officials General in the criminal justice system regarding the authority to make authentic deeds?. The connection between a Notary's deed and the occurrence of a criminal act is that the authentic deed and its protocol are used as evidence of a criminal act or if there is a criminal element in its preparation which is the Notary's fault or the parties' error in providing information; or there is an agreement made between the Notary and one of the presenters. Legal protection for Notaries as Public Officials in the criminal justice system in the form of the rights and obligations of the Notary, and the approval of the Notary's Honorary Council to take photocopies of the minutes of the deed and/or letters attached to the minutes of the notary's deed or protocol in the Notary's custody; and the Notary to attend examinations relating to the Notary's deed or protocol which is in the Notary's custody. The Notary Honorary Council carries out examinations of Notaries regarding criminal allegations related to authentic deeds. It is recommended that Notaries in carrying out their duties act honestly, carefully, independently, impartially, and safeguard the interests of the parties. The guidance and supervision of Notaries by the Notary Honorary Council should be further improved, as an effort to prevent the execution of authentic deeds related to criminal acts.